2020
DOI: 10.1007/s10840-020-00789-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and cardiac arrhythmias: a global perspective on arrhythmia characteristics and management strategies

Abstract: Background Cardiovascular and arrhythmic events have been reported in hospitalized COVID-19 patients. However, arrhythmia manifestations and treatment strategies used in these patients have not been well-described. We sought to better understand the cardiac arrhythmic manifestations and treatment strategies in hospitalized COVID-19 patients through a worldwide crosssectional survey. Methods The Heart Rhythm Society (HRS) sent an online survey (via SurveyMonkey) to electrophysiology (EP) professionals (physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
174
0
17

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(198 citation statements)
references
References 13 publications
7
174
0
17
Order By: Relevance
“…There have only been few reported cases of complete heart block [4,5]. It is difficult to determine if cardiac arrhythmias that are reported in patient cohorts are related to myocarditis, electrolyte abnormalities, or medication side effects as many of the medications administered to treat the infection are associated with arrhythmia [6]. This patient presented with complete heart block and was not given any therapeutics for COVID-19 prior to her hospitalization suggesting a different etiology causing her heart block.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There have only been few reported cases of complete heart block [4,5]. It is difficult to determine if cardiac arrhythmias that are reported in patient cohorts are related to myocarditis, electrolyte abnormalities, or medication side effects as many of the medications administered to treat the infection are associated with arrhythmia [6]. This patient presented with complete heart block and was not given any therapeutics for COVID-19 prior to her hospitalization suggesting a different etiology causing her heart block.…”
Section: Discussionmentioning
confidence: 98%
“…Cardiac arrhythmias have been reported in association with cardiac injury [2,4,5]. In a large physician survey predominantly involving electrophysiologists, sinus bradycardia and complete heart block were the most observed bradyarrhythmia in hospitalized patients [6]. The exact mechanism as to how COVID-19 causes cardiac injury remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation was the most common cardiac arrhythmia observed in patients with COVID-19 infection according to one survey [27]. The mechanisms that might cause atrial fibrillation in these patients are possibly due to systemic infection, direct viral cardiomyocyte injury, hypoxemia, and susceptibility of the population due to advanced age and their comorbidities, and, finally, sympathetic nervous system overactivity [28].…”
Section: Arrhythmias In Covid-19mentioning
confidence: 99%
“…The efficacy of chloroquine and hydroxychloroquine, which act as immunomodulating agents by modifying the pH of endocytic vesicles (so blocking the first infection phases), is a matter of debate. Indeed, several studies focused their attention on the increased risk of prolongation of QTc and possible onset of arrhythmias that these compounds, especially in combination with antibiotics, seem to induce (13). On the other hand, a meta-analysis conducted on nine different studies sustained the efficacy of these drugs (14).…”
Section: Introductionmentioning
confidence: 99%